Immune responses induced by Clostridium difficile. (October 2016) - Péchiné, Séverine; Collignon, Anne
Abstract: The spectrum of Clostridium difficile infections is highly variable, ranging from asymptomatic carriage to fatal colitis depending on the strain virulence and on the host, its gut microbiota and its immune response. After disruption of the gut microbiota, C. difficile pathogenesis can be divided into three steps: 1) contamination by spores and their germination; 2) multiplication of vegetative cells and intestinal colonization using colonization factors; 3) production of the toxins TcdA and TcdB, and for some strains, the binary toxin, which are responsible for the clinical signs. Three lines of defense counteract C. difficile . The first line is the epithelial barrier, which is breached by the toxins. Then, a rapid innate immune response follows, which forms the second line of defense. It provides very quick defense reactions against C. difficile but is non-specific and does not confer memory. C. difficile and its virulence factors, the toxins and colonization factors, induce a highly pro-inflammatory response, which can be either beneficial or harmful, but triggers the adaptive immunity as the third line of defense required to control the infectious process. Adaptive immunity provides a highly specific immune response against C. difficile with memory and long lasting immunity. The innate and adaptive immune responses against the toxins and surface components are analyzed as well as their role in disease susceptibility, severity and recurrences. Highlights: Toxins and surface proteins trigger innate and adaptive immune responses. TcdA and TcdB have Rho-GTPase-independent activities on IECs and immune cells. Surface proteins display immunomodulating properties through TLR4 and TLR5. Antibody responses are associated with favorable outcome and absence of recurrence.